Care For Your Budgerigar. - Thomas, Heather; Royal Society for the Prevention of Cruelty to Animals (London : Collins, 2005)
This title in the RSPCA pet care series, relaunched with completely revised and updated content and fresh new covers, is written by animal experts, to provide an illustrated guide with all the practical advice needed to care for your pet.
Previous ed.: 1990.
Includes index.
Editor, Heather Thomas.
Keywords: Budgerigar; Pets